High frequency ultrasound with color Doppler in dermatology - Elisa de Oliveira Barcaui; Antonio Carlos Pires Carvalho; Flavia Paiva Proença Lobo Lopes; Juan Piñeiro-Maceira; Carlos Baptista Barcaui (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Ultrasonography is a method of imaging that classically is used in dermatology to study changes in the hypoderma, as nodules and infectious and inflammatory processes. The introduction of high frequency and resolution equipments enabled the observation of superficial structures, allowing differentiation between skin layers and providing details for the analysis of the skin and its appendages. This paper aims to review the basic principles of high frequency ultrasound and its applications in different areas of dermatology.